Catholicism and Its Civic Engagement: case studies of the Catholic Church in Hong Kong, Macau, Taipei, and Shanghai - Hao, Zhidong (Review of Religion and Chinese Society, 2014)
The levels of civic engagement in terms of social services and civic activism in the Catholic churches of Hong Kong, Macau, Taipei, and Shanghai are very different. While the former three churches have a higher level of social services, Shanghai does not. Hong Kong has a higher level of civic activism than the other three dioceses. This paper explains the similarities and differences among these cities by using an analytical model of political, cultural, and individual opportunity structures. Our findings and analysis are derived from a collaborative research project on the Catholic Church’s civic engagement in the four cities using both quantitative and qualitative research methods. In a time of rapid political, economic, and social transformation in China, religion is beginning to play an increasingly important role. Our study sheds light on what roles Catholicism or other religions might play in this process, and it has important implications for church-state relations in greater China.